High-sensitivity microsatellite instability assessment for the detection of mismatch repair defects in normal tissue of biallelic germline mismatch repair mutation carriers. Issue 4 (7th September 2019) - González-Acosta, Maribel; Marín, Fátima; Puliafito, Benjamin; Bonifaci, Nuria; Fernández, Anna; Navarro, Matilde; Salvador, Hector; Balaguer, Francesc; Iglesias, Silvia; Velasco, Angela; Grau Garces, Elia; Moreno, Victor; et al.
Abstract : Introduction: Lynch syndrome (LS) and constitutional mismatch repair deficiency (CMMRD) are hereditary cancer syndromes associated with mismatch repair (MMR) deficiency. Tumours show microsatellite instability (MSI), also reported at low levels in non-neoplastic tissues. Our aim was to evaluate the performance of high-sensitivity MSI (hs-MSI) assessment for the identification of LS and CMMRD in non-neoplastic tissues. Materials and methods: Blood DNA samples from 131 individuals were grouped into three cohorts: baseline (22 controls), training (11 CMMRD, 48 LS and 15 controls) and validation (18 CMMRD and 18 controls). Custom next generation sequencing panel and bioinformatics pipeline were used to detect insertions and deletions in microsatellite markers. An hs-MSI score was calculated representing the percentage of unstable markers. Results: The hs-MSI score was significantly higher in CMMRD blood samples when compared with controls in the training cohort (p<0.001). This finding was confirmed in the validation set, reaching 100% specificity and sensitivity. Higher hs-MSI scores were detected in biallelic MSH2 carriers (n=5) compared with MSH6 carriers (n=15). The hs-MSI analysis did not detect a difference between LS and control blood samples (p=0.564). Conclusions: The hs-MSI approach is a valuable tool for CMMRD diagnosis, especially in suspected patients harbouring MMR variants of unknown significance or non-detected biallelic germline mutations.